Denial and Fear: Psychological Analysis of Covid-19 Information in a Czech Fundamentalistic Catholic Journal - Moravec, Pavel (Open theology, 2021)
The aim of the research was to analyze information about Covid-19 as it relates to religion in a fundamentalist Catholic periodical and to point out places in the articles that are not supported by scientific facts. We also examined whether the Covid-19 information found contained some coping strategies to deal with the pandemic situation. The object of the study was the Czech monthly Regina in the year 2020. Thematic analysis was used as a method. Two main themes were found - Trivialization and Combat between Good and Evil. At first, the disease was underestimated, from the September issue it was presented as a sign of the end times. The theme of Trivialization was divided into two subthemes: Exaggerated restrictions and Covid-19 is not the only problem of mankind. This theme was assigned to coping strategy Denial. The theme of Combat between Good and Evil was divided into three subthemes: Sign of the End Times, Evil’s quest to establish a new world order, and Vaccination breaks the relationship with God. This theme was assigned to a coping strategy Marking Religious Boundaries. The texts possessed much unfounded information stimulating fear and anxiety instead of active coping strategies to promote the reader’s hope of improving the epidemiological situation.